Lonomia caterpillar envenoming in French Guiana reversed by the Brazilian antivenom: A successful case of international cooperation for a rare but deadly tropical hazard. (1st September 2018) - Mayence, C.; Mathien, C.; Sanna, A.; Houcke, S.; Tabard, P.; Roux, A.; Valentin, C.; Resiere, D.; Lemonnier, D.; Nkont Cho, Flaubert; Hommel, D.; Fan, H.W.; et al.
Abstract: In the American continent, larval forms (caterpillars) of the Lonomia genus can cause systemic reactions in human beings. In this Paper, we report the third case of Lonomia envenoming recorded in French Guiana in 25 years, and the first in which specific antivenom was administered. Severe symptoms of the envenoming were observed in our patient including pain; coagulopathy and systemic hemorrhage. They are caused by skin contact with caterpillars. Recovery, however, was quite satisfactory thanks to the international cooperation of the health authorities in both France and Brazil. Highlights: Clinical symptoms of envenoming by caterpillars include pain, coagulopathy and systemic hemorrhage. We report a case of hemorrhagic syndrome due to Lonomia envenoming in French Guiana. Bleeding and coagulation disturbances were reversed with Brazilian Lonomia antivenom. Cooperation between Brazilian and French government institutions was essential to use Lonomia antivenom.